2014
DOI: 10.1111/ajag.12136
|View full text |Cite
|
Sign up to set email alerts
|

Are older Western Australians exposed to potentially inappropriate medications according to the Beers Criteria? A 13‐year prevalence study

Abstract: PIM exposure remains high in older Western Australians. Our findings identify patients most at risk and medications to consider on Australia-specific PIM lists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
5
24
0
6
Order By: Relevance
“…On average, the PIM initiators accumulated 2.8 different PIMs over the entire 12‐year study period. That finding is in line with an Australian study that found the mean number of different PIMs taken was 2.2 during a 13‐year study period …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On average, the PIM initiators accumulated 2.8 different PIMs over the entire 12‐year study period. That finding is in line with an Australian study that found the mean number of different PIMs taken was 2.2 during a 13‐year study period …”
Section: Discussionsupporting
confidence: 88%
“…In both age groups, the risk of PIM initiation was also higher in the second lowest income compared to the lowest income group. As expected, excessive polypharmacy was also strongly associated with PIM initiation in our study, which is consistent with previous studies . In addition, our finding of the higher risk of PIM initiation with the use of other psychotropics (than were listed in Meds75+ database) was in line with previous studies …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…‡ Conditional logistic regression models were adjusted for the following time‐dependent variables: nursing home status at the case or control time; hospital days, overall Charlson Comorbidity Index and general practitioner (GP) coverage percentage, all for the previous year; and a drug consumption profile for the preceding 90 days (plus the case or control date), which included the number of broad medication categories involved, the overall number of daily doses consumed (for any drug) and a count of daily doses for each broad drug category. § The overall prevalence of each potentially inappropriate medication (PIM) in the study population has been reported in a separate publication . ¶ Average annual GP coverage was obtained from patients' proportion of GP coverage over 1993–2005, where each GP visit was allocated a 61‐day coverage period (adjacent and overlapping periods being merged together).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have examined the prevalence of drugs from the Beers list in elderly populations, whereas others have concentrated on the association between Beers medications and adverse health outcomes. For example, our own previous work in this field suggests that Western Australians aged ≥65 years were prescribed six to seven different types of drugs annually (on average) during 1993–2005, and that 40–47% were exposed to Beers medications every year . Furthermore, older people were 18% more likely to have an unplanned hospitalization when exposed to these drugs …”
Section: Introductionmentioning
confidence: 99%